Continual Decline in Azole Susceptibility Rates in Candida tropicalis Over a 9-Year Period in China - Wang, Yao; Fan, Xin; Wang, He; Kudinha, Timothy; Mei, Ya-Ning; Ni, Fang; Pan, Yu-Hong; Gao, Lan-Mei; Xu, Hui; Kong, Hai-Shen; Yang, Qing; Wang, Wei-Ping; et al. (Frontiers in Microbiology, 2021)
Background: There have been reports of increasing azole resistance in Candida tropicalis, especially in the Asia-Pacific region. Here we report on the epidemiology and antifungal susceptibility of C. tropicalis causing invasive candidiasis in China, from a nine-year surveillance study. Methods: From August 2009 to July 2018, C. tropicalis isolates (n=3702) were collected from 87 hospitals across China. Species identification was carried out by mass spectrometry or rDNA sequencing. Antifungal susceptibility was determined by Clinical and Laboratory Standards Institute disk diffusion (CHIF-NET10-14, n=1510) or Sensititre YeastOne (CHIF-NET15-18, n=2192) methods. Results: Overall, 22.2% (823/3702) of the isolates were resistant to fluconazole, with 90.4% (744/823) being cross-resistant to voriconazole. In addition, 16.9% (370/2192) and 71.7% (1572/2192) of the isolates were of non-wild-type phenotype to itraconazole and posaconazole, respectively. Over the nine years of surveillance, the fluconazole resistance rate continued to increase, rising from 5.7% (7/122) to 31.8% (236/741), while that for voriconazole was almost the same, rising from 5.7% (7/122) to 29.1% (216/741), with no significant statistical differences across the geographic regions. However, significant difference in fluconazole resistance rate was noted between isolates cultured from blood (27.2%, 489/1799) and those from non-blood (17.6%, 334/1903) specimens (P value <0.05), and amongst isolates collected from medical wards (28.1%, 312/1110) versus intensive care units (19.6%, 214/1092) and surgical wards (17.9%, 194/1086) (Bonferroni adjusted P value <0.05). Although echinocandin resistance remained low (0.8%, 18/2192) during the surveillance period, it was observed in most administrative regions, and one third (6/18) of these isolates were simultaneously resistant to fluconazole. Conclusions: The continual decrease in the rate of azole susceptibility among C. tropicalis strains has become a nationwide challenge in China, and the emergence of multi-drug resistance could pose further threats. These phenomena call for effective efforts in future interventions.